POLITIK MULTIKULTIKULTURALISME DALAM NOVEL KANCING YANG TERLEPAS KARYA HANDRI T.M. - WISNU MURTI, INDRA; Eko Retnosari, Ira (Buana Bastra, 2019)
One of literature form that can be examined related to the results of what the authorwanted to tell is a novel. The novel chosen in this study was Kancing yang Terlepas byHandry T.M. This novel is interesting because it was written by a Semarang writer "originallyJavanese" not the descent of Chinese, and it told about a Chinese woman with various curvesof life in Indonesia, which in the past had politically unstable for the Chinese descendants tolive here.The purpose of this study was to describe the things that related in the politics ofmulticulturalism in Kancing yang Terlepas novel by Handry T.M. The theory used in thisresearch was the political theory of multiculturalism from Will Kymlicka. The politics ofmulticulturalism is the politics of recognition. Political recognition here means not only toaccept the diversity that exists but also appreciate, respect, even celebrate the diversity. Themethod used in this research was qualitative method. Data collection techniques useddocumentation, and the data analysis techniques used in this research are; classify,